2003
DOI: 10.1080/1462220031000094114
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nicotine on heart dimensions and blood volume in male and female rats

Abstract: The adverse effects of tobacco smoking on the cardiovascular system are well established. Effects of nicotine on the heart, in contrast, are not well characterized. Understanding specific effects of nicotine on the heart and on blood volume is relevant to (a) elucidating the mechanisms by which nicotine may contribute to heart disease and (b) determining potential risks associated with nicotine products used in smoking cessation or to treat various medical conditions. The present experiment investigated effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
3
9
0
Order By: Relevance
“…Fourth, because this is a clinical study, we did not have the evidence of direct harmful effects of the nicotine on the RA. Previous animal studies have shown the possible mechanisms of harmful effects of nicotine on the RA, which involved atrial fibrosis via downregulation of miR‐133 and miR‐590 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, because this is a clinical study, we did not have the evidence of direct harmful effects of the nicotine on the RA. Previous animal studies have shown the possible mechanisms of harmful effects of nicotine on the RA, which involved atrial fibrosis via downregulation of miR‐133 and miR‐590 …”
Section: Discussionmentioning
confidence: 99%
“…Previous animal studies have shown the possible mechanisms of harmful effects of nicotine on the RA, which involved atrial fibrosis via downregulation of miR-133 and miR-590. [40][41][42]…”
mentioning
confidence: 99%
“…) and animal studies (Elliott et al. , ) based on CS/nicotine exposures. Overall, males and females exhibited differential sensitivity for acute WPS exposure in the C57BL/6J and BALB/cJ mouse strains, and females exhibited increased susceptibility to pulmonary toxicity compared to males in both the strains.…”
Section: Discussionmentioning
confidence: 99%
“…Heusch and Maneckjee 1998;Crowley-Weber et al 2003) and cerebro-or cardiovascular risk (e.g. Chalon et al 2000;Hakki et al 2002;Elliott et al 2003;Fang et al 2003;West et al 2003;reviewed in Benowitz and Gourlay 1997;Benowitz 1998Benowitz , 2003. Furthermore, nicotine is an addictive agent and the development of tolerance can lead to the stressful symptoms of withdrawal in the absence of continued nicotine dosing (reviewed in Benowitz 1998).…”
Section: Nicotine As a Prototypic Agonistmentioning
confidence: 98%